Relationship types among adolescent parents participating in a home-visiting program: A latent-transition analysis. - Raskin, Maryna.; Fosse, Nathan E.; Fauth, Rebecca.; Bumgarner, Erin.; Easterbrooks, M. Ann. (Tufts University. Tisch Library., 2017)
Young parents (less than 25 years of age) have been shown to have especially low rates of father involvement and union stability. However, research has also shown that parenting experiences of young fathers may not be uniform. There is a need for more research that assesses both the multidimensionality of relationship typologies and their temporality. Using a large longitudinal sample of low-income, young mothers enrolled in a randomized control study of a home-visitation program (n = 704; 61% program, 39% control), we evaluated how mother-father relationship dynamics changed over time. Ten mother-reported indicators of relationships (e.g., coresidence, marital status, types of father support) were used to conduct a latent-class analysis of relationship types. A 4-class solution was identified at each time point: Single Parent, Supportive Nonresident Partner, Supportive Resident Partner, and Questioning/Ambivalent Coupling. Latent-transition analyses were used to evaluate stability of relationships across 2 years. At each transition, a large proportion of women moved from one relationship class to another, indicating heterogeneity in relationship dynamics of adolescent parents. Results revealed the potential of a home-visiting program targeted at young parents to favorably promote more stable and supportive mother-father relationships and coparenting arrangements. ©American Psychological Association, 2016. This paper is not the copy of record and may not exactly replicate the authoritative document published in the APA journal. Please do not copy or cite without author's permission. The final article is available, upon publication, at: http://dx.doi.org/10.1037/fam0000164.